The future of work: work values of Generation Z - Lee, Lineker Hock Huat (2024)
The concept of a diverse workforce is fascinating and challenging since this historical coexistence is unique in corporate culture, resulting in a melting pot of beliefs, cultures, and personal values. Generation Z (Gen Z) is entering the workforce during the ‘Great Resignation’ and has become increasingly accustomed to quitting jobs. This study examines the attitudes of Gen Z employees to work values that bring about organisational success in the context of generational differences among a Gen Z workforce. It also considers whether employee engagement moderates the relationship between Gen Z’s work values and organisational success. The Maslow’s hierarchy of needs and person-organisation fit theories were applied to explain employees' interactional relationships and the congruency between their work and company values. A mixed-methods approach comprised quantitative surveys with 221 respondents and semi-structured qualitative interviews with three human resource practitioners. It was found that understanding and responding to work values was critical to attracting, engaging, and retaining Gen Z employees. A shift in the evolving landscape towards making use of technology resonates with Gen Z’s values, and it is likely that the evolving environment was a significant macro factor in managing and engaging a Gen Z workforce. Furthermore, mental wellness impacted Gen Z causing it to disengage, and empirical evidence cited employee engagement as a mediator construct to reengage the disengaged Gen Z workforce.